INVESTMENT QUALITY IN SERANG REGENCY PARADOXAL REVIEW OF HIGH UNEMPLOYMENT - Abrianto, Abrianto (LPPM Universitas Bina Bangsa, 2024)
The percentage of open unemployment rate in Serang Regency in the last two years occupies the top position in Banten Province. The role of investment in Serang Regency in creating jobs has not been felt by the community significantly, this study aims to stimulate an increase in the quality of investment so that it can have a positive impact in efforts to reduce the unemployment rate in Serang Regency. The research method uses a qualitative approach based on in-depth observation. The results of this study present strategies that can be implemented to reduce the unemployment rate in Serang Regency through improving the quality of investment.